Seedling Growth Analysis of Papaya Cultivated on Several Planting Media Enriched by Plant Growth Promotor Microbes - Dewi Fatria; Andre Sparta; Deni Emilda; Bambang Hariyanto; Tri Budiyanti; Martias Martias; Mizu Istianto (Universitas Sebelas Maret, 2021)
There are factors contributed to the growth and development of fruit crop seedling. Microbes are well known as plant growth promotors such as symbiotic mycorrhizae and antagonist fungi, Trichoderma spp. The main objective of this experiment is to find out the best medium composition enriched by beneficial microbes to improve papaya seedling growth. The experiment was conducted at Sumani Experimental Station, Indonesian Tropical Fruit Research Institute, Solok, West Sumatera, Indonesia from August until December 2017. The experiment was arranged in a Randomized Complete Block Design with ten treatments and three replicate blocks. The treatments were ten combinations of media for papaya seedling growth enriched by plant growth promotor microbes. In this experiment, medium soil with additional manure, rice husk charcoal and compost (single or combination) combined with mycorrhizae were used. Also, the effect of Trichoderma sp. enrichment into media composition were tested in this experiment. Treatments SCRMc and SCRMcT; with its complexity; were the best media composition to promote papaya seedling growth. These treatments resulted in best performance of plant height, stem diameter and number of leaves of papaya seedlings. The additional of Trichoderma sp. into medium did not show beneficial effect for all parameters in this experiment.